The indiscriminate and off label use of Ritalin - Galucio, Natasha Costa da Rocha (2021)
Methylphenidate hydrochloride [(dl-treo-metil-2-fenil-2- (2-piperidil) acetato], known as Ritalin, is a psychotropic drug commonly used by people with Attention Deficit Hyperactivity Disorder (ADHD) and narcolepsy for its treatment. As it is a drug that acts on the nervous system by releasing norepinephrine and dopamine in the synaptic clefts, causing an excitation in postsynaptic receptors and altering the user's cognitive functions, the off label use to improve cognitive performance is becoming more and more common. This type of medication must be used rationally, as well as any other medication, as they can cause adverse effects and dependence. In view of the above, this study aimed to evaluate, through the literature, the correct way to use methylphenidate, the indiscriminate use, off label and the health problems that prolonged use can trigger in the user, as well as the importance of pharmaceutical care for effective treatment with methylphenidate. For this, an integrative literature review was carried out and the articles for this review were collected in the following search portals: SciELO, BVS and Lilacs. After collection, 21 studies were selected to compose the results. It was possible to notice that the indiscriminate use of methylphenidate hydrochloride has been carried out frequently by many people, especially by students, which can lead to serious complications and the appearance of serious adverse effects, especially cardiovascular events such as tachycardia and hypertension, psychiatric disorders such as depression, psychosis and chemical dependency, as well as the neurological system such as dyskinesia, involuntary muscle contractions and spasms, among others.